Epistemology of Maqasid Taha Abdurrahman; New Paradigm and Classification of Maqasid al-Shari'ah Values - Aspandi Aspandi; Nurul Ma'rifah; Ahmad Hidayat; Mochamad Abdul Ghofur; Ahmad Dzulfikar (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
Taha Abdurrahman, a contemporary maqasid figure, has different concepts and ideas from the Shatibi maqasid concept. The concept of maqasid Taha Abdurrahman also has a paradigm and classification of values that are different from the concept of maqasid Shatibi. This study aims to describe the paradigm of reform of maqasid values according to Taha Abdurrahman. In addition, this study also describes the classification of new maqasid values according to Taha Abdurrahman. This research uses a qualitative approach that explains and analyzes the concepts and ideas of maqasid al-shari'ah reform according to Taha Abdurrahman. This research uses a library method with the main data source of Taha Abdurrahman's work entitled Tajdid al-Manhaj fi Taqwim al-Turath, and Su’al al-Manhaj fi Ufuqi al-Ta’sisi Liunmudhaji Fikri Jadidi. The results of this study show that the paradigm of reform of maqasid values according to Taha Abdurrahman is based on the hadith of the Prophet “Innama Buitstu Liutamimma Makaarimal Akhlak” which is holistic in nature encompassing all levels of needs that are an integral part of Islamic law. The classification of new maqasid values according to Taha Abdurrahman is contained in the concept of “al-qiyam al-akhlaqiyyah” Include al-masalih al-hayawiyyah, al-masalih al-‘aqliyyah, and al-masalih al-ruhiyyah namely maqasid values with dimensions of materialism, rationalism, and spiritualism. Taha Abdurrahman's classification of maqasid al-shari'ah revises the conception of the Shatibi maqasid.